Rancang Bangun Aplikasi Pemantauan Produksi Drum pada PT.Karya Bakti Metalasri - Bagus, Andrew; Soebijono, Tony; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
the purpose of the thesis was to produce a steel drum production monitoring applications in PT. Karya Bakti Metalasri (PT. KBM), which can assist in the processing and recap of the production’s report. Drum production monitoring application using waterfall method. Waterfall method is that each stage of the system will be done sequentially decreased from the communication, planning, modeling, construction, dan deployment. Based on the test results, this application can help the PT. KBM in processing and recap report production also accelerate the process of making daily or monthly production report.